2006
DOI: 10.1038/sj.emboj.7600970
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a flavonoid glucosyltransferase reveals the basis for plant natural product modification

Abstract: Glycosylation is a key mechanism for orchestrating the bioactivity, metabolism and location of small molecules in living cells. In plants, a large multigene family of glycosyltransferases is involved in these processes, conjugating hormones, secondary metabolites, biotic and abiotic environmental toxins, to impact directly on cellular homeostasis. The red grape enzyme UDP-glucose:flavonoid 3-Oglycosyltransferase (VvGT1) is responsible for the formation of anthocyanins, the health-promoting compounds which, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
474
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(505 citation statements)
references
References 42 publications
24
474
0
7
Order By: Relevance
“…rol1-1, a nonsense mutation at position 318; rol1-2, a missense distinct UDP-sugar specificity allowed us to deduce the amino acid residues involved in substrate recognition. The three-dimensional structure of grape (Vitis vinifera) flavonoid 3-O-glucosyltransferase (3GlcT) was determined, and a structural analysis suggests the presence of several key residues that interact with UDP-sugar and the flavonoid backbone (Offen et al, 2006). The amino acids Gln-375, Asp-374, and Thr-141 have been proposed to interact with hydroxyl groups at the C-2 and C-3, C-3, and C-4, and C-6 positions of the glucose moiety of UDPglucose, respectively, but Gln-375 and Thr-141 are not conserved in the Arabidopsis 3GlyTs (see Supplemental Figure 3 online).…”
Section: A Flavonol Glycosyltransferase:flavonol 3-o-arabinosyltransfmentioning
confidence: 99%
“…rol1-1, a nonsense mutation at position 318; rol1-2, a missense distinct UDP-sugar specificity allowed us to deduce the amino acid residues involved in substrate recognition. The three-dimensional structure of grape (Vitis vinifera) flavonoid 3-O-glucosyltransferase (3GlcT) was determined, and a structural analysis suggests the presence of several key residues that interact with UDP-sugar and the flavonoid backbone (Offen et al, 2006). The amino acids Gln-375, Asp-374, and Thr-141 have been proposed to interact with hydroxyl groups at the C-2 and C-3, C-3, and C-4, and C-6 positions of the glucose moiety of UDPglucose, respectively, but Gln-375 and Thr-141 are not conserved in the Arabidopsis 3GlyTs (see Supplemental Figure 3 online).…”
Section: A Flavonol Glycosyltransferase:flavonol 3-o-arabinosyltransfmentioning
confidence: 99%
“…For example, His366, Asp374 and Asp390 are predicted to play an important role as a catalytic domain of UGTs, based on site-directed mutagenesis and computer modeling experiments [17,18,22]. Recent investigations on crystal structures of glucosyltransferases from Medicago truncatula [19,20] and Vitis vinifera [21] confirmed that these amino acids are key players in UDP-glucose recognition. However, potential roles in the overall glucose transfer reaction of less well-conserved amino acids within an individual UGT have attracted little attention.…”
Section: Site-directed Mutagenesis Of Caugt2mentioning
confidence: 99%
“…Investigation of the 3D-structures of betanidin 5-O-glucosyltransferase (B5GT) from Dorotheanthus bellidiformis [17] and cyanohydrin glucosyltransferase from Sorghum bicolor [18] by homology modeling, and of isoflavonoid 3 0 -O-glucosyltransferase from Medicago truncatula [19,20] and flavonoid 3-O-glucosyltransferase from Vitis vinifera [21] by X-ray crystallography, revealed the role of specific conserved amino acid residues in the PSPG-box that constitute the donor-sugar binding pockets. However, the roles of less well conserved amino acids within the motif that may determine the characteristics unique to particular enzymes such as substrate recognition and catalytic potential have been less closely examined.…”
Section: Introductionmentioning
confidence: 99%
“…This role of Arg-140 is consistent with a generally accepted theory of enzymatic catalysis, which is called the "transition state fitting theory" (Pauling, 1948;Copeland, 2000; see Supplemental Results 1 online for details). Moreover, in the model of the Vv GT5-R140W docked with ligands (see Supplemental Figure 3 online), due to the absence of Arg-140, the carboxylate of UDP-GA points to His-20, which corresponds to the catalytically important His-20 of Vv GT1 (Offen et al, 2006). This interaction takes His-20 away from the 3-OH group of flavonol substrates and likely impairs the role of His-20.…”
Section: Online)mentioning
confidence: 99%
“…These results suggest plasticity of the mechanisms that alter the sugar donor specificity of UGTs. To examine the molecular basis for the specificity of Vv GT5 for UDP-GA, a three-dimensional structural model of Vv GT5 docked with UDP-GA and a flavonol (kaempferol) was constructed using the crystal structure of Vv GT1 as a template ( Figure 4A) (Offen et al, 2006). The structural model predicted an interaction between the guanidinium group of Arg-140 of Vv GT5 and the carboxyl group of the glucuronic acid moiety of bound UDP-GA. A sequence comparison showed that Arg-140 of Vv GT5 is replaced by a Trp residue in each UGT examined, which, for example, corresponds to Trp-140 in Vv GT1 and Vv GT6 ( Figure 4C).…”
Section: Identification Of a Residue That Critically Determines The Smentioning
confidence: 99%